Perbandingan Hasil Intracytoplasmic Sperm Injection (ICSI) antara Azoospermia Obstruktif dan Non-Obstruktif ‘Literatur Review’ - Nurma Nurma; Azniah Azniah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Intra Cytoplasmic Sperm Injection (ICSI) is a reproductive technique used to help couples who have fertility problems, especially those caused by sperm factors. This procedure involves placing one sperm that has been selected by an embryologist using a microscope with a magnification of 400x, where one sperm cell is injected into 1 mature and normal egg cell using a microscopic needle. The ICSI technique is often used in couples who have fertility problems caused by poor sperm count, motility, or shape. This study uses the Literature review method by examining various basic sources of electronic data such as PubMed, Google Scholar. The following search strategy was modified for various basic data and search engines.